Enabling Robotic Process Automation (RPA) in Talent Acquisition Process - A case study - Mai, Trinh (My University, 2026)
Digitalization and automation are transforming HR operations; however, many Talent Acquisition (TA) activities continue to be discontinuous and manually managed. At company B, TA utilizes various methods and extensive administrative efforts while encountering pressure to achieve accelerated and consistent hiring results. This study examines the potential of Robotic Process Automation (RPA) to enhance the TA process at case company B, focusing on increasing efficiency while preserving human judgment. The research builds on existing literature about information systems design, criteria for RPA task compatibility, and human-centered digital human resources. It emphasizes initial-stage talent acquisition processes that are high-volume, repetitive, rule-based, and dependent on structured digital inputs, including the information exchanges across the applicant tracking system (ATS), human resources information systems (HRIS), and office applications. A qualita-tive embedded single-case research approach was employed. Empirical data were gathered through semi-structured interviews with recruiters, hiring managers, and HR support employ-ees, an open-ended qualitative survey of 20 participants engaged in talent acquisition and associated roles, and internal process documentation. The data were thematically categorized and analyzed to define current TA process, identify significant bottlenecks, and evaluate which tasks fulfill the stated RPA applicability criteria. Company B had not used RPA in Talent Acquisition throughout the study period. The empirical research therefore guides a conceptual, consultancy-oriented process redesign instead of assessing an existing automation solution. The results indicate that inefficiencies arise from disjointed technologies, redundant data in-put, and considerable manual coordination, particularly in three subprocesses: CV screening and eligibility assessment, interview scheduling, and the preparation and transfer of onboard-ing and requisition data. These domains demonstrate strong suitability for automation, how-ever final applicant evaluation, interviews, assessment of compatibility and motivation, wage negotiation, and unusual instances should continue to be conducted by humans. The thesis proposes RPA-enabled workflows across three sub-processes and proposes them as suggested future designs for Company B, contending that these structures might enhance TA efficiency when executed with appropriate governance.
Keywords: automation; processes; personnel administration; human resource management; organisations (systems); data systems; robotics; Strategic Project Management; Master’s Programme in Strategic Business Development